Infants and the decision to provide ongoing child welfare services - Joanne Filippelli; Barbara Fallon; Nico Trocmé; Esme Fuller-Thomson; Tara Black (BMC, 2017)
Abstract Background Infants are the most likely recipients of child welfare services; however, little is known about infants and families who come into contact with the child welfare system and factors that are associated with service provision. Investigations involving infants and their families present an unparalleled opportunity for the child welfare sector to enhance infants' safety and well-being through early identification, referral and intervention. Understanding how the child welfare system responds to the unique needs of infants and caregivers is critical to developing appropriate practice and policy responses within the child welfare sector and across other allied sectors. This study examines maltreatment-related investigations in Ontario involving children under the age of one to identify which factors are most influential to predicting service provision at the conclusion of a child welfare investigation. Methods A secondary analysis of the fifth cycle of the Ontario Incidence Study of Reported Child Abuse and Neglect (OIS) for 2013 was conducted. The OIS is a cross-sectional child welfare study that is conducted every 5 years. The most influential factors that were associated with the decision to transfer a case to ongoing services were explored through a multivariate tree-classification technique, Chi square automatic interaction detection. Results There were an estimated 7915 maltreatment-related investigations involving infants in 2013. At least one caregiver risk factor was identified in approximately three-quarters (74%) of investigations involving infants. In the majority of investigations (57%), at least one referral for specialized services was provided. Primary caregiver with few social supports was the most highly significant predictor of the decision to provide ongoing child welfare services. Primary caregiver risk factors were predominant in this model. The analysis identified subgroups of investigations involving infants for which the likelihood of being transferred to ongoing services ranged from approximately 11-97%. Conclusion Caregivers of infants are struggling with numerous challenges that can adversely compromise their ability to meet the unique developmental needs of their infant. The findings underscore the importance of community and social supports in decision-making.